AN EVALUATION ON THE ATTITUDES OF STUDENTS FOR PR EDUCATION AND IDENTIFYING FACTORS RELATING TO PROFESSION IMAGE: A SURVEY ON STUDENTS STUDYING AT PR DEPARTMENTS - Cihan BECAN (Fırat University, 2019)
The education of public relations has started to play an important role as PR has been needed by both private and public sector. With that PR industry has been becoming widespread all around Turkey over the last two decades, it is required to discuss about the programme and content of PR education. In reference to previous years, the ever - increasing number of PR departments all across both of Istanbul and Turkey shows that it needs to be focused on basic PR education. The main of the study is to identify the attitudes of students, studying at public relations at associate and undergraduate level, about the education of PR in their own universities. While dealing the problematic of this research, the survey will be applied to 546 students studying at four universities having PR departments, on the scale of Istanbul, with the simple random sampling method through face-to-face questionnaire. This research will be studied between February 13th and March 20th, 2017. The fact that all universities in Istanbul cannot be reached is limitedness for this survey because of the fact that time and budget has been restricted. With regard to the result of the study, it is proved that ‘practical experience’ firstly comes as the basic factor among the attitude factors. Also, it is verified that there is positively relationship between attitudes of students towards PR education and types of university and programme they are studying. It also clearly shows that students largely benefit from traditional lectures, i